Belowground Inoculation With Arbuscular Mycorrhizal Fungi Increases Local and Systemic Susceptibility of Rice Plants to Different Pest Organisms - Bernaola, Lina; Cosme, Marco; Schneider, Raymond W.; Stout, Michael (Frontiers in Plant Science, 2018)
Plants face numerous challenges from both above-ground and below-ground stressors, and defend themselves against harmful insects and microorganisms in many ways. Because plant responses to biotic stresses are not only local but also systemic, below-ground interactions can influence above-ground interactions in both natural and agricultural ecosystems. Arbuscular mycorrhizal fungi (AMF) are soilborne organisms that form symbiotic associations with many plant roots and are thought to play a central role in plant nutrition, growth, and fitness. In the present study, we focused on the influence of AMF on rice defense against pests. We manipulated the inoculation of rice plants by AMF in several field and greenhouse experiments to test whether the interaction of AMF with rice roots changes the resistance of rice against two chewing insects, the rice water weevil (Lissorhoptrus oryzophilus Kuschel, RWW) and the fall armyworm (Spodoptera frugiperda, FAW), and to infection by sheath blight (Rhizoctonia solani, ShB). Both in field and greenhouse experiments, the performance of insects and the pathogen on rice was enhanced when plants were inoculated with AMF. In the field, inoculating rice plants with AMF resulted in higher numbers of RWW larvae on rice roots. In the greenhouse, more RWW first instars emerged from AMF-colonized rice plants than from non-colonized control plants. Weight gains of FAW larvae were higher on rice plants treated with AMF inoculum. Lesion lengths and susceptibility to ShB infection were higher in rice plants colonized by AMF. Although AMF inoculation enhanced the growth of rice plants, the nutritional analyses of root and shoot tissues indicated no major increases in the concentrations of nutrients in rice plants colonized by AMF. The large effects on rice susceptibility to pests in the absence of large effects on plant nutrition suggest that AMF colonization influences other mechanisms of susceptibility (e.g. defense signaling processes). This study represents the first study conducted in the U.S. in rice showing AMF-induced plant susceptibility to several antagonists that specialize on different plant tissues. Given the widespread occurrence of AMF, our findings will help to provide a different perspective into the causal basis of rice systemic resistance/susceptibility to insects and pathogens.